Metagenomic analysis of the medicinal leech gut microbiota - Maltz, Michele A. (Frontiers Media S.A., 2014)
There are trillions of microbes found throughout the human body and they exceed the number of eukaryotic cells by 10-fold. Metagenomic studies have revealed that the majority of these microbes are found within the gut, playing an important role in the host's digestion and nutrition. The complexity of the animal digestive tract, unculturable microbes, and the lack of genetic tools for most culturable microbes make it challenging to explore the nature of these microbial interactions within this niche. The medicinal leech, Hirudo verbana, has been shown to be a useful tool in overcoming these challenges, due to the simplicity of the microbiome and the availability of genetic tools for one of the two dominant gut symbionts, Aeromonas veronii. In this study, we utilize 16S rRNA gene pyrosequencing to further explore the microbial composition of the leech digestive tract, confirming the dominance of two taxa, the Rikenella-like bacterium and A. veronii. The deep sequencing approach revealed the presence of additional members of the microbial community that suggests the presence of a moderately complex microbial community with a richness of 36 taxa. The presence of a Proteus strain as a newly identified resident in the leech crop was confirmed using fluorescence in situ hybridization (FISH). The metagenome of this community was also pyrosequenced and the contigs were binned into the following taxonomic groups: Rikenella-like (3.1 MB), Aeromonas (4.5 MB), Proteus (2.9 MB), Clostridium (1.8 MB), Eryspelothrix (0.96 MB), Desulfovibrio (0.14 MB), and Fusobacterium (0.27 MB). Functional analyses on the leech gut symbionts were explored using the metagenomic data and MG-RAST. A comparison of the COG and KEGG categories of the leech gut metagenome to that of other animal digestive-tract microbiomes revealed that the leech digestive tract had a similar metabolic potential to the human digestive tract, supporting the usefulness of this system as a model for studying digestive-tract microbiomes. This study lays the foundation for more detailed metatranscriptomic studies and the investigation of symbiont population dynamics.